DEVELOPING MULTIMEDIA BASED LEARNING MATERIAL FOR TEACHING SPEAKING TO GRADE EIGHT STUDENTS OF SMP NEGERI 1 TABANAN - ., MADE PUTRI ARI SUSANTHI; ., PROF. DR. I NYM. ADI JAYA PUTRA, M.A.; ., DRS. I WAYAN SUARNAJAYA, M.A., P.hD (Jurnal Pendidikan Bahasa Inggris Indonesia, 2015)
This study focused at developing multimedia based learning material for teaching speaking for grade eight students. This study was focused on: (1) developing multimedia based learning material for teaching speaking; (2) knowing teacher’s response toward the implementation of digital storytelling; (3) knowing students’ responses toward the implementation of digital storytelling. The subjects of this study were grade eight students of SMP N 1 Tabanan. The data were obtained questionnaires, interviews and observations. Based on the findings of this study, it was concluded that (1) the digital storytelling for teaching speaking could be developed through need analysis, designing a prototype, experts judgments, revising the product, field testing, and final product, (2) the result of teacher’s response about the implementation of digital storytelling was good, (3) and the result of students’ responses about the implementation digital storytelling was good. It can be said that the product of multimedia is good to be used for teaching speaking.Kata Kunci : Digital Storytelling, Material Development and Speaking Skill Penelitian ini bertujuan untuk mengembangkan multimedia pembelajaran untuk pembelajaran berbicara bagi siswa kelas VIII di SMP N 1 Tabanan. Secara spesifik focus penelitian ini; 1) mengembangkan multimedia pembelajaran untuk pengajaran berbicara; 2) mengetahui respon guru terhadap impelementasi digital storytelling; 3) mengetahui respon siswa terhadap impelementasi digital storytelling. Data dikumpulkan melalui observasi, wawancara dan kuesioner. Berdasarkan temuan penelitian ini, disimpulkan bahwa (1) Media digital storytelling untuk pembelajaran berbicara dapat dikembangkan melalui analisis kebutuhan, merancang prototipe, penilaian ahli, merevisi produk, pengujian lapangan dan produk akhir, (2) Hasil respon guru mengenai pelaksanaan digital storytelling adalah baik, (3) dan hasil respon siswa mengenai pelaksanaan digital storytelling adalah baik. Dapat dikatakan bahwa produk multimedia ini baik untuk digunakan dalam pengajaran berbicara.keyword : Digital Storytelling, Pengembangan Materi dan Berbicara